2019
DOI: 10.1111/bcpt.13187
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of prenatal nicotine exposure and post‐weaning high‐fat diet on hypercholesterolaemia in rat offspring of different sexes

Abstract: Hypercholesterolaemia is considered a disease with intrauterine origin. Recently, we reported that prenatal nicotine exposure (PNE) induced an abnormal level of total cholesterol in rat offspring before and after birth. However, there were little data about sex differences in serum cholesterol level in PNE offspring. In addition, many previous studies reported that blood cholesterol is associated with daily diet. This study was designed to analyse the interaction among PNE, high-fat diet (HFD) and sex on chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…According to the World Health Organization, more than 1 billion people around the world smoke, and 5 million die from cigarettes each year. In China, the current smoking rate for adults, aged 15 and over, is 27.7, percent and the total number of smokers is more than 300 million (China Adult Tobacco Survey, 2015). Even though the rate of active smoking during pregnancy in China is relatively low, the exposure rate to secondhand smoke during pregnancy is alarmingly high (>50%) [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization, more than 1 billion people around the world smoke, and 5 million die from cigarettes each year. In China, the current smoking rate for adults, aged 15 and over, is 27.7, percent and the total number of smokers is more than 300 million (China Adult Tobacco Survey, 2015). Even though the rate of active smoking during pregnancy in China is relatively low, the exposure rate to secondhand smoke during pregnancy is alarmingly high (>50%) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine levels in the amniotic fluid can exceed maternal plasma levels by 88% [8,9]. Perinatal nicotine exposure is harmful to the health of the offspring in many aspects; it results in low birth weight, preterm delivery, stillbirth, neurobehavioral deficits, sudden infant death syndrome, and a range of neuroendocrine, craniofacial, and immune system abnormalities [10][11][12][13][14][15][16]. In addition to these problems, it is especially harmful to the developing respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that perinatal programmed offspring can be affected by a “second hit,” such as HFD that exacerbates their cardiometabolic health in a sex‐specific manner. 18 , 19 , 20 , 21 , 22 , 23 In these studies, the researchers focused on peripheral mechanisms, such as renal function, glucose homeostatic response, and systemic and adipose renin‐angiotensin system (RAS), that are involved in the sex differences in cardiometabolic dysfunction in offspring with both prenatal insult and postnatal HFD feeding. Although a large body of studies have shown central interactions between sex hormones and the RAS, proinflammatory cytokines (PICs), and leptin influencing SNS activity and BP, 15 , 24 , 25 , 26 , 27 , 28 , 29 the mechanisms underlying central regulatory effects of sex hormones, especially estrogen regulation of autonomic function in HFD fed offspring of maternal hypertensive dams, have not been explored.…”
mentioning
confidence: 99%